A contract perspective on the international finance facility - Tun Lin; George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
The present paper is a first attempt to develop a theoretical model using a short-term vis-à-vis long-term contract framework within which donor countries' endorsement or rejection decision towards the recently proposed International Finance Facility (IFF) is rationalized. The current foreign aid system is portrayed as being similar to a series of short-term contracts, where donor countries are able to adjust the aid amount to reflect environmental change (broadly defined to take into account changes in public opinion, domestic situation, etc.). The benefit of this system is in its flexibility. Frontloading aid, on the other hand, as proposed by the IFF proposal, has the benefit of smoothing out the flows over time. In the model presented in this paper, donor countries balance these two contract schemes to determine the endorsement or rejection of the IFF proposal. By using historical aid data covering the period 1990-2003 for all DAC donor countries, our empirical analysis shows the payoffs and relative advantages of these two contract schemes.
Keywords: F35; D81; 330; foreign aid; International Finance Facility; contract theory; uncertainty; Entwicklungshilfe; Internationale Finanzierung; Vertragstheorie